Electrochemical Mechanism and Structure Simulation of 2D Lithium‐Ion Battery. Issue 10 (26th June 2018) - Dai, Mingzhi; Huo, Changhe; Zhang, Qiang; Khan, Karim; Zhang, Xingye; Shen, Cai
Abstract: For decades, lithium batteries have attracted much attention. Highly efficient, safe, and convenient batteries are worthy of being investigated and applied in modern life. However, most of the investigation is on the macroscopic device electrical properties such as current–voltage curves. Investigation on the microscopic electrical properties including potential distribution, electrolyte salt concentration distribution, and lithium ion concentration distribution within the batteries during the discharging is still needed. Here, a detailed study of the key electrical properties distributions inside the lithium battery in the discharging status is given. After comparing three widely used cathode materials (LiCoO2, LiMn2 O4, and LiFePO4 ), LiFePO4 is found to show the most stable working performance which is consistent with previous reports. This is probably attributed to its most uniform key electrical properties distributions, its high electric conductivity, and crystal structure. A structure is also proposed which might give a hint to stress and temperature release for a longer and safer application of batteries. This simulation study on the key parameters distribution inside the battery may help to achieve a better understanding and hence control on the lithium battery performance and reliability. Abstract : The key electrical properties distributions inside lithium batteries including electrolyte potential, electrolyte concentration, and lithium ion concentration, together with an updated battery structure design, are simulated and investigated to improve battery performance and reliability. This study might give a hint to select cathode materials and design battery electrode structures for an improved battery performance and reliability.